EXPRESS: Use of subconjunctival cyclosporine implants for treatment of feline eosinophilic keratoconjunctivitis: a case report - Lynn Willems; Jordan Kay Roberts (Journal of Feline Medicine and Surgery Open Reports, 2026)
Case summary A 5-year-old neutered male domestic shorthair cat was presented for evaluation of chronic bilateral eosinophilic keratoconjunctivitis (EK). The patient had a history of recurrent corneal plaques and conjunctivitis that were initially managed with systemic and topical immunosuppressive therapy. Long-term disease control was limited by poor tolerance of topical ophthalmic medications, resulting in inconsistent treatment and repeated disease recurrence affecting both eyes. Over several years the cat was treated with subconjunctival triamcinolone acetonide, antiviral therapy, and topical megestrol acetate with only partial and temporary improvement. Due to persistent disease and inability to administer long-term topical therapy reliably, bilateral subconjunctival cyclosporine implants were surgically placed. Postoperative management included short-term topical antibiotic therapy. At the 10-week and 7-month postoperative examinations, marked clinical improvement was observed, with resolution of most corneal plaques and substantial reduction in conjunctival inflammation. Relevance and novel information Feline eosinophilic keratoconjunctivitis is a chronic immune-mediated ocular surface disease that typically requires long-term topical immunosuppressive therapy. Successful management may be limited in patients that are resistant to medication administration. This case demonstrates that subconjunctival cyclosporine implants may represent a viable long-acting treatment option for feline EK when topical therapy cannot be consistently administered. To the authors’ knowledge, use of cyclosporine implants for management of feline eosinophilic keratoconjunctivitis has not previously been reported.